(untitled) (International journal of artificial intelligence, 2026)
The article examines the problem of developing students’ skills in literary text analysis in the process of studying literature at university. Special attention is paid to the methods and techniques of developing analytical skills, as well as to the pedagogical conditions ensuring the effectiveness of this work. It is concluded that literary text analysis serves as an important means of forming students’ philological competence and analytical thinking.